Evidence for mean free path fluctuation induced pinning in YBa2Cu3O7 and YBa2Cu4O8 films - Griessen, R. (1994)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Katholieke Universiteit Leuven. Laboratorium voor Vaste Stof Fys-ika en Magnetisme; Bélgica